Recommended immunization schedule for children and adolescents: Immunization Guideline (8th edition) released by the Korean Pediatric Society in 2015 - Jong-Hyun Kim; Eun Hwa Choi; Su Eun Park; Yae-Jean Kim; Dae Sun Jo; Yun-Kyung Kim; Byung-Wook Eun; Jina Lee; Soo-Young Lee; Hyunju Lee; Ki Hwan Kim; Kyung-Hyo Kim (Korean Pediatric Society, 2016)
This report includes the recommended immunization schedule table for children and adolescents based on the 8th (2015) and revised 7th (2012) Immunization Guidelines released by the Committee on Infectious Diseases of the Korean Pediatric Society (KPS). Notable revised recommendations include: reorganization of the immunization table with a list of vaccines on the vertical axis and the corresponding age on the horizontal axis; reflecting the inclusion of Haemophilus influenzae type b vaccine, pneumococcal conjugate vaccine, and hepatitis A vaccine into the National Immunization Program since 2012; addition of general recommendations for 2 new Japanese encephalitis (JE) vaccines and their interchangeability with existing JE vaccines; addition of general recommendations for quadrivalent meningococcal conjugate vaccines and scope of the recommended targets for vaccination; and emphasizing catch-up immunization of Tdap vaccine. Detailed recommendations for each vaccine may be obtained from the full KPS 8th Immunization Guidelines.